2010
DOI: 10.1002/ejic.201000855
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Reactions of Molybdenum and Tungsten Hydride Complexes Containing the Tetraphosphane Ligand mesoo‐C6H4(PPhCH2CH2PPh2)2

Abstract: The reaction of [Mo(κ2‐dppe)(κ4‐P4)] (1a) {dppe = PPh2CH2CH2PPh2, P4 = meso‐o‐C6H4(PPhCH2CH2PPh2)2} with 1 atm of H2 at room temperature selectively gave [MoH2(κ2‐dppe)(κ3‐P4)] (3a). The W analogue of 1a reacted with 1 atm of H2 at 80 °C to form a mixture of [WH2(κ2‐dppe)(κ3‐P4)] and [WH4(κ4‐P4)] (5b), the latter of which could be cleanly prepared by the reduction of [WBr2(κ4‐P4)] with NaBH4 in ethanol at 50 °C. The molecular structure of complex 5b differed from that of the related complex [WH4(dppe)2] and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Although various nitriles insert into the W–H bonds of 1 , this pathway is unlikely to lead to the tetrameric chain that contains no additional H atoms. On the other hand, 1 is capable of liberating two H 2 to generate a coordinatively unsaturated W(0) species with high electron-donating ability. , It is reasonable to postulate that two molecules of highly electron-accepting Ar F CN undergo reductive C–C coupling on this W center to yield the tungstacyclodiimine ring (or its resonance structure κ 2 -diimido complex) as illustrated in Scheme . A similar five-membered metallacycle formation from Zr(II) and p -tolunitrile has been reported by Bercaw et al, and a doubly N-protonated product (diimine complex) has been prepared through reduction of an Fe–MeCN complex by Mutterties and co-workers .…”
Section: Resultsmentioning
confidence: 99%
“…Although various nitriles insert into the W–H bonds of 1 , this pathway is unlikely to lead to the tetrameric chain that contains no additional H atoms. On the other hand, 1 is capable of liberating two H 2 to generate a coordinatively unsaturated W(0) species with high electron-donating ability. , It is reasonable to postulate that two molecules of highly electron-accepting Ar F CN undergo reductive C–C coupling on this W center to yield the tungstacyclodiimine ring (or its resonance structure κ 2 -diimido complex) as illustrated in Scheme . A similar five-membered metallacycle formation from Zr(II) and p -tolunitrile has been reported by Bercaw et al, and a doubly N-protonated product (diimine complex) has been prepared through reduction of an Fe–MeCN complex by Mutterties and co-workers .…”
Section: Resultsmentioning
confidence: 99%
“…7 Our previous studies on Mo and W complexes have revealed structures and reactivity specific to P4, and recently the tetrahydride complex [WH 4 (k 4 -P4)] (3) has been synthesized. 8 The structure of 3 is different from the analogous complex [WH 4 (dppe) 2 ] in some points, and moreover, the reactivity of 3 is much higher than [WH 4 (dppe) 2 ], probably owing to a highly strained geometry around the W centre and the ability of P4 to change hapticity. 9 Subsequent study on the reactions of 3 with CS 2 and RNC (R = Bu t , 2,6-Me 2 C 6 H 3 ) has resulted in isolation of [W(k 2 -S 2 CH 2 )(k 4 -P4)] and [W(CNR) 2 (k 4 -P4)], proving that 3 is not only a strong hydride donor but also a good precursor of coordinatively unsaturated species.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that double hydride insertion takes place in the reaction of 3 with a related heterocumulene CS 2 to give [W(k 2 -S 2 CH 2 )(k 4 -P4)] 8. Although the result of the reaction with ArNCS appears contrasting, a mechanism involving the corresponding complex [W(k 2 -13d Complex 3 reacted with alkyl isothiocyanates in different ways, and the products could not be identified.…”
mentioning
confidence: 99%
“…We have been investigating the coordination chemistry of the linear tetradentate phosphine ligand meso-o-C 6 H 4 (PPhCH 2 CH 2 PPh 2 ) 2 (P4) using its Mo and W complexes [M(κ 2 -dppe)(κ 4 -P4)] (M = Mo (1), W; dppe = Ph 2 PCH 2 CH 2 PPh 2 ) as the precursors. 2 Research on reactivity toward various small molecules such as nitriles, isocyanides, CO, 3 H 2 , 4 CO 2 , and iso-thiocyanates 5 has revealed that the terminal PPh 2 groups in P4 readily dissociate to generate open coordination sites. In contrast, two internal P atoms maintain metal-P bondings owing to the rigid o-phenylene linkage and, as a result, the denticity of P4 changes between κ 4 , κ 3 , and κ 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also advantageous that the other ligands are hydride and Cp, which are sterically much smaller than any sets of dppe with a certain two-electron donor as widely seen in previously synthesized complexes. [3][4][5] This may allow the second metal atom trapped by the terminal PPh 2 to approach the Mo center easily. In this work, the reactivity of 2 at the Mo center is examined, and efficient formation of early-late bimetallic complexes is † Electronic supplementary information (ESI) available: X-ray crystallographic data in CIF format, additional information and diagrams of crystallographic studies, and NMR spectra of new compounds.…”
Section: Introductionmentioning
confidence: 99%